Status of implementation and organization of cancer screening in The European Union Member States—Summary results from the second European screening report - Basu, Partha; Ponti, Antonio; Anttila, Ahti; Ronco, Guglielmo; Senore, Carlo; Vale, Diama Bhadra; Segnan, Nereo; Tomatis, Mariano; Soerjomataram, Isabelle; Primic Žakelj, Maja; Dillner, Joakim; Elfström, Klara Miriam; et al. (International journal of cancer, 2018)
The second report on the implementation status of cancer screening in European Union (EU) was published in 2017. The report described the implementation status, protocols and organization (updated till 2016) and invitation coverage (for index year 2013) of breast, cervical and colorectal cancer screening in the EU. Experts in screening programme monitoring (N = 80) from the EU Member States having access to requisite information in their respective countries provided data on breast, cervical and colorectal cancer screening through online questionnaires. Data was collected for screening performed in the framework of publicly mandated programmes only. Filled in questionnaires were received from 26 Member States for all three sites and from one Member State for breast cancer only. Substantial improvement in screening implementation using population‐based approach was documented. Among the age‐eligible women, 94.7% were residents of Member States implementing or planning population‐based breast cancer screening in 2016, compared to 91.6% in 2007. The corresponding figures for cervical cancer screening were 72.3 and 51.3% in 2016 and 2007, respectively. Most significant improvement was documented for colorectal cancer screening with roll‐out ongoing or completed in 17 Member States in 2016, compared to only five in 2007. So the access to population‐based screening increased to 72.4% of the age‐eligible populations in 2016 as opposed to only 42.6% in 2007. The invitation coverage was highly variable, ranging from 0.2–111% for breast cancer, 7.6–105% for cervical cancer and 1.8–127% for colorectal cancer in the target populations. In spite of the considerable progress, much work remains to be done to achieve optimal effectiveness. Continued monitoring, regular feedbacks and periodic reporting are needed to ensure the desired impacts of the programmes. What's new? In 2003 the European Union (EU) Council urged member states to devote greater attention to breast, cervical, and colorectal cancer screening. The second report on progress in this regard was published in 2017. The present manuscript details implementation status, protocol, and organization of screening programs and screening invitation coverage of target populations in member states. The data show that within a decade, the proportion of eligible EU populations having access to breast, cervical, and colorectal cancer screening increased by 5.8, 11.9 and 33.6 percent respectively. Future Council recommendations may need to consider the incorporation of alternative screening strategies.